Clinical and Radiographic Outcomes From Repeat Whole-brain Radiation Therapy for Brain Metastases in the Age of Stereotactic Radiosurgery. (June 2016) - Guo, Susan; Balagamwala, Ehsan H.; Reddy, Chandana; Elson, Paul; Suh, John H.; Chao, Samuel T.
Abstract : Objectives: Repeating whole-brain radiation therapy (WBRT) in patients with progressive/recurrent brain metastases is controversial. We retrospectively reviewed our experience of repeat WBRT in an era where stereotactic radiosurgery was also available. Methods: In our IRB-approved database, 49 patients received repeat WBRT from 1996 to 2011. Median initial dose of WBRT was 30 Gy in 10 fractions (range, 27 to 37.5 Gy); median reirradiation dose was 20 Gy in 10 fractions (range, 14 to 30 Gy). Median Karnofsky performance status (KPS) at reirradiation was 70 (range, 40 to 90). Median number of discrete lesions at reirradiation was 6 (range, 1 to 30). Median interval between initial diagnosis of brain metastases and relapse requiring repeat WBRT was 11.5 months (range, 1.5 to 49.2 mo). Overall survival and relapse-free survival were summarized using the Kaplan-Meier method. The log-rank test was used to compare outcomes between groups. Results: Ninety percent of patients completed repeat WBRT. Median survival after repeat WBRT was 3 months (95% CI, 1.9-4.0). Thirteen patients had improved neurological symptoms (27%), 12 were stable (24%), and 14 had worsening symptoms (29%). On radiographic follow-up of 22 patients, 10 (46%) were improved, 4 (18%) were stable, and 8 (36%) progressed. Improved neurological symptoms after repeat WBRT and higher KPS at first follow-up were associated with improved survival ( P =0.05 and 0.02). Conclusions: Repeat WBRT was well tolerated. Modest survival times are seen. Prognostic factors for survival include improved neurological symptoms after repeat WBRT and higher KPS at first follow-up. Repeat WBRT may be useful to improve neurological symptoms in patients with limited treatment options, especially those who are not appropriate stereotactic radiosurgery candidates.